Recessive mutations in DGKE cause atypical hemolytic-uremic syndrome - Lemaire, Mathieu; Frémeaux-Bacchi, Véronique; Schaefer, Franz; Choi, Murim; Tang, Wai Ho; Le Quintrec, Moglie; Fakhouri, Fadi; Taque, Sophie; Nobili, François; Martinez, Frank; Ji, Weizhen; Overton, John D.; et al. (Nature genetics, 2013)
Richard Lifton, Véronique Frémeaux-Bacchi and colleagues report that recessive mutations in DGKE cause atypical hemolytic-uremic syndrome with an early age of onset progressing to chronic kidney disease. The authors propose that loss of DGKE results in a prothrombotic state that underlies disease pathogenesis.